2021
DOI: 10.1177/0956462420981527
|View full text |Cite
|
Sign up to set email alerts
|

Assessing community pharmacists’ involvement and clients’ opinion on HIV/AIDS services in community pharmacies in Nigeria: a cross-sectional survey

Abstract: The World Health Organization is promoting community-based services to end HIV/AIDS by 2030. In Nigeria, studies on community pharmacists’ involvement in HIV testing services (HTS) and antiretroviral (ARV) medication therapy management (MTM) are scarce, and no study had evaluated the clients’ opinion on community pharmacy HTS. We assessed the community pharmacists’ involvement in HIV/AIDS services and clients’ opinions of community pharmacy HTS. Semi-structured questionnaires on a five-point Likert scale were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…One effectiveness study, a randomized trial, explored the effect of HIV self‐testing (HIVST) vouchers redeemable at varying prices and distribution sites, including private pharmacies in urban areas, on service uptake [ 41 ]. Four studies explored the feasibility of [ 19 , 42 , 43 , 44 ] and two studies explored the acceptability of [ 45 , 46 ] of this HIV testing service delivery model. The studies measured all effectiveness and feasibility outcomes post‐implementation and acceptability outcomes pre‐implementation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One effectiveness study, a randomized trial, explored the effect of HIV self‐testing (HIVST) vouchers redeemable at varying prices and distribution sites, including private pharmacies in urban areas, on service uptake [ 41 ]. Four studies explored the feasibility of [ 19 , 42 , 43 , 44 ] and two studies explored the acceptability of [ 45 , 46 ] of this HIV testing service delivery model. The studies measured all effectiveness and feasibility outcomes post‐implementation and acceptability outcomes pre‐implementation.…”
Section: Resultsmentioning
confidence: 99%
“…A pilot study in South Africa that found pharmacy‐delivered HIVST feasible also found that many clients who tested HIV positive already knew their HIV status [ 42 ]. The studies assessing acceptability, both qualitative, found that Ugandan men anticipated higher uptake of HIVST at a pharmacy versus other community delivery models [ 45 ] and that Nigerian pharmacy clients and providers were generally willing to engage in pharmacy‐delivered HIV testing services [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations